2016
DOI: 10.5384/sjovs.vol9i2p1-7
|View full text |Cite
|
Sign up to set email alerts
|

Fusional stamina: An alternative to Sheard’s criterion

Abstract: Sheard postulated that symptoms from heterophoria can be avoided if the fusional reserves in the opposite direction are at least twice the size of the phoria itself; this is known as “Sheard’s criterion”. Although later studies have provided supporting evidence for this postulate, dichotomous criteria of this type are subject to a lack of sensitivity since small differences in measurements can result in a change in classification. The main purpose of this study was to provide a reliable continuous altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
6
2
Order By: Relevance
“…Vergence measures have been suggested to vary with race, ethnicity and age. 19 Specifically for race, the mean findings of heterophoria in the present study are comparable to those from other African populations 10,13 (Table 5) 11,10,12,31,8,24,42,26,14,27,23,21,4,22,15,25,16,20,19 ; the slight differences may be because of those studies 11,13 that enrolled younger schoolchildren. Furthermore, different phoria dissociation methods were used in some studies.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Vergence measures have been suggested to vary with race, ethnicity and age. 19 Specifically for race, the mean findings of heterophoria in the present study are comparable to those from other African populations 10,13 (Table 5) 11,10,12,31,8,24,42,26,14,27,23,21,4,22,15,25,16,20,19 ; the slight differences may be because of those studies 11,13 that enrolled younger schoolchildren. Furthermore, different phoria dissociation methods were used in some studies.…”
Section: Discussionsupporting
confidence: 75%
“…Aligned to heterophoria and fusional vergences is Sheard's criterion, which is a good indicator of symptoms. 46 The 6.5% failure rate of Sheard's criterion in this study is lower than the 12.5% found by Myklebust et al 42 in Norwegian schoolchildren, while the 4.6 mean convergence ratio found is comparable to 4.45 pd by Lanca and Rowe in Portugal. 23 The findings on the association of phorias and refractive errors from previous studies are diverse, 37,38,39,40,41,42 which may be related to different study designs and criteria applied to define variables.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Regarding the opposite fusion vergence NFV, the mean difference to blur, break and recovery points was p = 0.025, p = 0.022, and p = 0.026, respectively, which was statistically significant. Myklebust and Riddell reported that there is a risk of missing decompensated heterophoria based only on passing Sheard's criterion and recommended that a continuous fusion persistence alternative may be useful for clinicians in quantifying binocular vision problems and monitoring treatment effects [12]. However, Moon et al [8] stated that Sheard's criterion is a useful tool for screening convergence insufficiency with exophoria associated with near vision activities.…”
Section: Discussionmentioning
confidence: 99%
“…The second intrasubject method was introduced by Sheard this technique related the heterophoria to its opposing fusional vergence blur point. It is stated that the opposing fusional reserve to the blur point should be at least twice the size of the phoria [1], [11], [12]. Sheard assumed that symptoms from heterophoria (latent strabismus) can be avoided if the fusional reserves in the opposite direction are at least twice the size of the phoria [1], [4], [8].…”
Section: Introductionmentioning
confidence: 99%